2019
DOI: 10.1109/access.2019.2901932
|View full text |Cite
|
Sign up to set email alerts
|

The Negation of Basic Probability Assignment

Abstract: In many cases, we obtain information using various methods in order to make better decisions. The everything in nature and society has its negative, the negation of negation has significant meaning. Considering the problem from two aspects, we can get more accurate information. However, in most cases, the information of negation is ignored. Hence, the negation provides a new view to obtain information. However, existing negation method mainly apply to probability distribution. How to get the negation of basic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 85 publications
0
44
0
Order By: Relevance
“…It can be concluded that GIQ is more complicated with more information. It should be mentioned that a possible extension of GIQ is to deal with belief function, which is widely used in many real applications…”
Section: Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be concluded that GIQ is more complicated with more information. It should be mentioned that a possible extension of GIQ is to deal with belief function, which is widely used in many real applications…”
Section: Proposed Methodsmentioning
confidence: 99%
“…It can be concluded that GIQ is more complicated with more information. It should be mentioned that a possible extension of GIQ is to deal with belief function, 31 which is widely used in many real applications [51][52][53][54] Compared with the existing IQ, 30 some advantages of GIQ should be pointed out. IQ only considers the uncertainty of the probability itself and ignores the association of the collected sensor data.…”
Section: Calculate Credibilitymentioning
confidence: 99%
“…Basic belief assignment (BBA), a mass function, is one of the most basic and important definitions of D‐S evidence theory . normalΘ is known to identify the framework.…”
Section: Preliminariesmentioning
confidence: 99%
“…One assumption of evidence theory is the close world, which means the mass function of empty set is zero . In addition, due to the fact that the BPA is the most important concept of evidence theory, many operations such as belief structure, correlation, negation, entropy, and divergence are developed.…”
Section: Preliminariesmentioning
confidence: 99%